Manajemen Pembelajaran Tafsir Tarbawi dalam Nuansa Islam Moderat di Universitas KH. A. Wahab Hasbullah - Hilyah Ashoumi; Ahmad Nasrullah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2022)
The purpose of this study is to examine: 1) planning for learning moderate Islamic education in tafsir tarbawi courses at Universitas KH. A. Wahab Hasbullah 2) implementation of moderate Islamic education learning for tafsir tarbawi courses at Universitas KH. A. Wahab Hasbullah and 3) evaluation of learning moderate Islamic Education for tafsir tarbawi courses at Universitas KH. A. Wahab Hasbullah. The research method used is a qualitative method. Data collection through observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results showed that: 1) the planning of moderate Islamic education learning steps for decision-making steps agreement between lecturers and students on the existence of similarities in the Semester Learning Plan and material in the objectives so that learning planning is planned effectively and efficiently. 2) the implementation of moderate Islamic education learning, while the learning strategies used are active discussion / debate and problem-based learning. In the learning material of the tarbawi interpretation course, there are values of religious moderation. 3) the evaluation of moderate Islamic education learning carried out on an ongoing basis cannot be determined only from the results but must be viewed based on the process from beginning to end in order to find more comprehensive results.